Surface-Enhanced Raman Scattering (SERS) With Silver Nano Substrates Synthesized by Microwave for Rapid Detection of Foodborne Pathogens - Wei, Caijiao; Li, Mei; Zhao, Xihong (Frontiers in Microbiology, 2018)
The rapid and sensitive methods are developed to detect foodborne pathogens which are important to food safety. Therefore, the aim of this study is to explore surface enhanced Raman scattering with silver nano substrates to detect and identify the three foodborne pathogens which are Escherichia coli O157: H7, Staphylococcus aureus and Salmonella. All the cells were resuspended with 10 mL the silver colloidal nanoparticles making the concentration of 107 CFU/mL, and then were exposed to 785 nm laser excitation. In this study, the results showed that all the bacteria can be sensitively and reproducibly detected directly by SERS. The distinctive differences can be observed in SERS spectral data of three food-borne pathogens and the silver colloidal nanoparticles can be used as highly sensitive SERS-active substrates. In addition, the assay time just only required few minutes, which indicated that SERS coupled with the silver colloidal nanoparticles is a promising method for detection and characterization of food-borne pathogens. At the same time, the principle component analysis (PCA) and hierarchical cluster analysis (HCA) made the different bacterial strains can be clearly differentiated based on the barcode spectral data reduction. Therefore, the SERS methods hold great promise for detection and identification of food-borne pathogens and even for applications in food safety.